2000
DOI: 10.4049/jimmunol.164.4.2001
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Mediates CTLA-4 Suppression of Cellular Immunity in Murine Kalaazar

Abstract: Recent studies indicate important roles for CTLA-4 engagement in T cells, and for TGF-β production in the immunopathogenesis of murine kalaazar or visceral leishmaniasis, but a functional link between these two pathways in helping intracellular parasite growth is unknown. Here we report that Ag or anti-CD3 activation of splenic CD4+ T cells from visceral leishmaniasis leads to intense CTLA-4-mediated TGF-β1 production, as assessed either by CTLA-4 blockade or by direct CTLA-4 cross-linkage. Production of TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
108
2
3

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 37 publications
6
108
2
3
Order By: Relevance
“…In the spleen, the number of CD4 ϩ cells decreased by Ͼ50%, and CD4 ϩ cells analyzed ex vivo did neither proliferate spontaneously nor in response to anti-CD3. Treatment of such spleen cells from infected mice with anti-TGF-␤ did not restore immune suppression (data not shown), suggesting that TGF-␤ production by CTLA-4-positive cells is not linked to immune suppression in P. berghei malaria, as it was described for Leishmania infections (27).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In the spleen, the number of CD4 ϩ cells decreased by Ͼ50%, and CD4 ϩ cells analyzed ex vivo did neither proliferate spontaneously nor in response to anti-CD3. Treatment of such spleen cells from infected mice with anti-TGF-␤ did not restore immune suppression (data not shown), suggesting that TGF-␤ production by CTLA-4-positive cells is not linked to immune suppression in P. berghei malaria, as it was described for Leishmania infections (27).…”
Section: Discussionmentioning
confidence: 81%
“…CTLA-4 may also antagonize CD28 function by competing for B7 molecules, or by inhibiting CD28-mediated TCR reorganization. Finally, CTLA-4 triggering has been reported to induce the production of TGF-␤ (27). The effect of CTLA-4 blockade in vivo was first demonstrated in a tumor model in which an enhanced antitumor immunity was observed (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms of CTLA-4 suppression of T-cell activation are still undefined, a recent study demonstrated that engagement of CTLA-4 promotes the production of TGF-β by CD4 + T cells, while inhibiting the production of all other cytokines tested (Chen et al 1998). We found that splenic CD4 + T cells from kalazar secrete large amounts of TGF-β when stimulated by Leishmania antigen or mitogens, and that TGF-β secretion can be abolished by CTLA-4 blockade (Gomes et al 2000). Moreover, we demonstrated that CTLA-4 engagement suppresses T-cell IFN-γ production and promotes L. chagasi growth in cocultured Mφ through secretion of TGF-β (Gomes et al 2000).…”
mentioning
confidence: 87%
“…We found that splenic CD4 + T cells from kalazar secrete large amounts of TGF-β when stimulated by Leishmania antigen or mitogens, and that TGF-β secretion can be abolished by CTLA-4 blockade (Gomes et al 2000). Moreover, we demonstrated that CTLA-4 engagement suppresses T-cell IFN-γ production and promotes L. chagasi growth in cocultured Mφ through secretion of TGF-β (Gomes et al 2000). These results suggest that L. chagasi infection induces host T cells to produce TGF-β by driving them to a state of sustained CTLA-4 engagement.…”
mentioning
confidence: 94%